PERANCANGAN APLIKASI PEMESANAN DAN PERCETAKAN PADA PT SANGKAKALA INDAH MENGGUNAKAN METODE UCD (USER CENTRAL DESIGN) BERBASIS ANDROID - Sibarani, Sarina; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2023)
The development of technology today is very fast, without exception, both information and communication technology. Therefore, an efficient step is needed to anticipate it. Information and communication technology is now starting to enter various aspects of life, one of which is in the business world. This is because a lot of work is assisted by information technology which is able to minimize the level of errors even to the level of losses that will occur. PT Sangkakala Indah is a company engaged in the printing sector, namely serving the design of document notes, banners, banners and is currently facing problems in the field of ordering. The ordering system at PT Sangkakala Indah is still done conventionally. For example, in recording orders, making order invoices to taking orders and transaction reports, they still rely on recording on notes and the difficulty of communication between graphic designers and customers. This of course can cause loss or damage to the order data or sales transaction. \Digital printing is a printing method for producing printouts that are done using digital-based images or documents. With this method, documents or print applications can be processed quickly and easily. This digital printing is an innovation from its predecessor, offset printing, which is classified as wasteful of raw materials and production time. Digital printing has advantages such as producing sharp print and color applications, lower costs, being able to print in small quantities, and being able to streamline production timeUser centered design (UCD) is called human centered design.